Translation and Canadian municipal websites: A Toronto Example - McDonough Dolmaya, Julie (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
Within translation studies, existing research on website translation and localization has tended to focus on technical, sociological, commercial and linguistic issues related to the websites of corporations or not-for-profit organizations. Less attention has been given to issues that arise when national, regional or local governments make their websites available in another language, either in whole or in part. To help address this gap, this article studies the Toronto.ca municipal website to discuss whether, how and why the City of Toronto offers translated information online. Drawing on data from the 2016 Canadian census and the city’s translation policy documents, this article compares the city’s linguistic profile with the kinds of information available on the city’s website in languages other than English. The final section uses De Schutter’s (De Schutter 2017) framework to study the City of Toronto’s translation policies from a translation justice perspective, arguing that the policies largely focus on instrumental interests, with limited emphasis on identity interests, as evidenced by the Toronto.ca translation data. Some possible future research directions are also discussed.